Health Literacy Promoting Guideline for Chronic Kidney Disease Prevention among Village Health Volunteers in Nonthaburi Province - ผดุงพัฒนากูล ทรงพล; จันทขัมมา นภาเพ็ญ; สุวรรณจินดา ดวงเดือน (Journal of Health Science of Thailand, 2026)
This research project aimed to examine the development process of two programs: a scientific literacy and health literacy enhancement program for the prevention of chronic kidney disease (CKD), and a capacity-building program to strengthen screening skills and health communication among village health volunteers (VHVs). This study also sought to propose practical guidelines for promoting health literacy in CKD prevention among VHVs. A qualitative research design was employed, with data collected through semi-structured focus group discussions with VHVs and analyzed using content analysis. The findings revealed two major guidelines for enhancing health literacy for CKD prevention among VHVs. The first guideline involved promoting changes in scientific literacy and health literacy through seven learning activities: (1) understanding the nature of science, (2) kidney and urinary system anatomy, (3) kidney functions, (4) accessing health information and services and media literacy, (5) healthy eating and physical activity for CKD prevention, (6) safe use of dietary supplements, and (7) self-management of health conditions to reduce CKD risk. The second guideline focused on strengthening screening competency and health communication skills through four activities: (1) discovering truths through active listening, dialogue, relationship building, and shared goal setting; (2) critical reflection; (3) making appropriate decisions regarding health practices; and (4) feedback and evaluation. The findings suggested that these guidelines might be applied to enhance health literacy among VHVs in other areas with similar contexts to support chronic kidney disease prevention in the community, especially while non-communicable diseases remain a significant public health concern in Thailand.